ALK-positive diffuse large B-cell lymphoma: report of four cases and review of the literature - Beltran, Brady (2009)
Background: Anaplastic lymphoma kinase-positive diffuse large B-cell lymphoma (ALK-DLBCL) is a rare lymphoma with several clinicopathological differences from ALK-positive anaplastic large cell lymphoma (ALCL). The latest WHO classification of lymphomas recognizes ALK-DLBCL as a separate entity. Methods: A comprehensive comparison was made between the clinical and pathological features of the 4 cases reported and those found in an extensive literature search using MEDLINE through December 2008. Results: In our series, three cases were adults and one was pediatric. Two cases had primary extranodal disease (multifocal bone and right nasal fossa). Stages were I (n = 1), II (n = 1), III (n = 1) and IV (n = 1). Two cases had increased LDH levels and three reported B symptoms. IPI scores were 0 (n = 1), 2 (n = 2) and 3 (n = 1). All cases exhibited plasmablastic morphology. By immunohistochemistry, cases were positive for cytoplasmic ALK, MUM1, CD45, and EMA; they marked negative for CD3, CD30 and CD20. Studies for EBV and HHV-8 were negative. The survival for the patients with stage I, II, III and IV were 13, 62, 72 and 11 months, respectively. Conclusion: ALK-DLBCL is a distinct variant of DLBCL with plasmacytic differentiation, which is characterized by a bimodal age incidence curve, primarily nodal involvement, plasmablastic morphology, lack of expression of CD20, aggressive behavior and poor response to standard therapies, although some cases can have prolonged survival as the cases reported in this study. ALK-DLBCL does not seem associated to immunosuppression or the presence of EBV or HHV8. Further prospective studies are needed to optimize therapies for this entity.